Potentials of straw return and potassium supply on maize (Zea mays L.) photosynthesis, dry matter accumulation and yield - Ya-fang Fan; Ju-lin Gao; Ji-ying Sun; Jian Liu; Zhi-jun Su; Shu-ping Hu; Zhi-gang Wang; Xiao-fang Yu (Scientific Reports, 2022)
Abstract Maize (Zea mays L.) is considered one of the most important grains in the world. Straw return has the effect of reducing soil bulk density and increasing soil porosity. Straw returning and potassium fertilizer can supplement soil potassium content. The improvement of soil structure and the optimization of soil nutrient levels provide a good environment for high yield and high efficiency of maize. Therefore, three field experiments were carried out over a three-year period (2018–2020) to study the effects of straw returning on photosynthesis, dry matter accumulation and yield of maize 'Xianyu 335' under two different fertilization methods and four potassium application levels. The results showed that straw returning and potassium application had significant effects on the above indicators. The above indicators were significantly improved by deep tillage straw returning compared with no tillage straw returning. Increasing potassium supply can promote the effect of straw returning. The photosynthesis, dry matter accumulation and yield parameters of maize treated with straw returning and deep tillage combined with 60 kg/hm2 potassium fertilizer (SFK60) reached the highest in the three harvest seasons. The corn planting profit of SFK45 treatment is the highest, which is $1868.92 per ha. Therefore, SFK45 is an effective way to ensure stable and high yield of corn and maximize farmers' income.